Experimental Measurements of Nanofluids Thermal Properties - Adnan, M. Husein; R. A., Bakar; K., Kadirgama; K. V., Sharma (Universiti Malaysia Pahang, 2013)
Solid particles dispersed in a liquid with sizes no larger than 100nm, known as nanofluids, are used to enhance Thermophysical properties compared to the base fluid. Preparations of alumina (Al2O3), titania (TiO2) and silica (SiO2) in water have been experimentally conducted in volume concentrations ranging between 1 and 2.5%. Thermal conductivity is measured by the hot wire method and viscosity with viscometer equipment. The results of thermal conductivity and viscosity showed an enhancement (0.5–20% and 0.5–60% respectively) compared with the base fluid. The data measured agreed with experimental data of other researchers with deviation of less than 5%. The study showed that alumina has the highest thermal conductivity, followed silica and titania, on the other hand silica has the highest viscosity followed alumina and titania.